Betting on Macau : casino capitalism and China's consumer revolution - Simpson, Tim (Associate professor) (Globalization and community, 2023)
"Examining the unprecedented scale of its development and its key role in China's economic revolution, Simpson follows Macau's emergence from historical obscurity to become the most profitable casino gaming locale in the world. In turn, his trenchant analysis provides a distinctive view into China's broader project of urbanization, its post-Mao economic reforms, and the continued rise of its consumer culture"--